PENGARUH KINERJA PELAKSANAAN PROGRAM PENURUNAN STUNTING TERHADAP TUMBUH KEMBANG ANAK BALITA DI KABUPATEN ROKAN HULU - yulia Febrianti; Amir Syamsuadi; Ade Febriani (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Post was designated as the only stunting locus area in the province Riau in 2017 Rokan Hulu Regency took various steps policy. These efforts are actualized by the efforts of the local government building collaborative synergies between regional government apparatus organizations in an integrated stunting reduction effort. This study analyzes and describes the role of cross-sectors in the convergence of the acceleration of decline Stunting in Rokan Hulu District. The approach in this research is qualitative research in the form of field research by collecting sources of primary data and secondary data through in-depth interviews and reviews document. The results of the research show that the Government of Rokan Hulu Regency carry out efforts to reduce stunting in a structured and comprehensive manner, such as: Identify the distribution of stunting, program availability, and constraints in the implementation of integrated nutrition interventions, develop an activity plan for improve the implementation of integration of nutrition interventions, organize consultations stunting, providing legal certainty for villages to carry out their roles and village authority in integrated nutrition interventions, ensuring the availability and the functioning of cadres who assist the village government in implementation integrated nutrition interventions at the village level, improving data management systems stunting and coverage of interventions, measuring growth and development of children under five and publication of stunting figures and conducting a review performance of program implementation and activities related to stunting reduction periodic. Implementation of the Program to Accelerate the Reduction of Stunting in Districts Rokan Hulu is viewed based on policy standards and targets; resource; inter-organizational communication and activity strengthening; the characteristics of the implementing agency; implementor disposition; and social, economic and political conditions.